2017
DOI: 10.1038/s41598-017-16323-3
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of the Majorana quasiparticles in the Rashba chain

Abstract: We demonstrate that the selective equal–spin Andreev reflection (SESAR) spectroscopy can be used in STM experiments to distinguish the zero–energy Majorana quasiparticles from the ordinary fermionic states of the Rashba chain. Such technique, designed for probing the p–wave superconductivity, could be applied to the intersite pairing of equal–spin electrons in the chain of magnetic Fe atoms deposited on the superconducting Pb substrate. Our calculations of the effective pairing amplitude for individual spin co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
(47 reference statements)
5
24
0
Order By: Relevance
“…Such 'intrinsic polarization' of the Majorana modes has been previously suggested in Ref. [46], and recently we have proposed [47] their empirical detection by means of the Selective Equal Spin Andreev Reflection (SESAR) spectroscopy.…”
Section: B Spin-polarized Majorana Quasiparticlessupporting
confidence: 56%
“…Such 'intrinsic polarization' of the Majorana modes has been previously suggested in Ref. [46], and recently we have proposed [47] their empirical detection by means of the Selective Equal Spin Andreev Reflection (SESAR) spectroscopy.…”
Section: B Spin-polarized Majorana Quasiparticlessupporting
confidence: 56%
“…Upon entering the topological phase, there appear two Majorana quasiparticles simultaneously in both spin channels but with different spectral weights, what has been indeed reported in the STM measurements using a ferromagnetic tip [12]. Such issue has been recently addressed by several groups [11,13,14]. J. Klinovaja with co-workers [8] have shown that spin up and down tunneling amplitudes between MBSs and quantum dot depend on the spin-orbit interaction length.…”
Section: Physical Setupmentioning
confidence: 72%
“…The first one is related to the spin polarization. For a proximized nanowire with homogeneous RSOC, the behavior of spin polarization has been shown to provide useful insights about the topological transition, and it has been recently suggested that the spin polarization of Majorana fermions could be exploited to distinguish them from ordinary fermion states of the nanowire [54,[83][84][85]. Let us compare this case to the spin polarization shown in Fig.5(a) that we find for a normal nanowire without proximity effect and with inhomogeneous RSOC.…”
Section: B Future Developmentsmentioning
confidence: 99%